Achilles in control? Managing oneself and others in the funeral games - Kelly, A (Cambridge University Press, 2017)
Though great poets may appreciate the artistry and interest of the Funeral Games in Book 23 of the Iliad, it must be admitted that the entire episode can seem an interlude between the death of Hector in Book 22 and the final, pathetic meeting between Achilles and Priam in Book 24. This ‘intermediate’ status has caused its own difficulties, and so the games tend to be one of the more understudied and/or oversimplified parts of the poem, either a ‘happy interlude’ to provide a final ‘curtain-call’ for its major figures, or a dark story which shows only the inability of the characters to change or avoid conflict over timê. Polarised readings of this sort underestimate the episode’s importance within the Iliad, either by using it as a mere introduction to a discussion of the final book or by cherry-picking its episodes in order to construct a picture of Homeric society as a whole, though they do at least focus our attention on conflict in the Iliad as a matter of both poetic form and social content.